1960
DOI: 10.58799/b-66
|View full text |Cite
|
Sign up to set email alerts
|

Summary of Pennsylvanian section in southwestern New Mexico and southeastern Arizona

Abstract: Pennsylvanian strata in southwestern NM and southeastern AZ range from Morrowan to Virgilian in age, are disconformable to angularly unconformable above Precambrian to Upper Mississippian rocks, and are as much as 4,000 ft thick, although in most localities they range from 1,000-2,000 ft in thickness. The Pennsylvanian-Permian contact in many areas appears to be gradational, and the boundary is drawn within a zone of indeterminate age between Virgilian and Wolfcampian fossil-bearing beds. Permian rocks at some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1964
1964
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…section thins, the clastic ratio increases, and the shales become red (Foster, 1964;Kottlowski, 1960b) and organically leaner, therefore losing their sourcerock potential.…”
Section: V I W E S T -C E N T R a L N E W M E X I C Omentioning
confidence: 99%
“…section thins, the clastic ratio increases, and the shales become red (Foster, 1964;Kottlowski, 1960b) and organically leaner, therefore losing their sourcerock potential.…”
Section: V I W E S T -C E N T R a L N E W M E X I C Omentioning
confidence: 99%
“…They are dominantly marine shales of variegated dark-gray, olive, and reddish colors. Many of the limestones are biostromal (Kottlowski, 1960b). The more favorable sandstones in the Sandia Formation have porosities in the 10-20% range (Reese, 1975).…”
Section: V S O U T H W E S T E R N N E W M E X I C Omentioning
confidence: 99%
“…He concluded that they were too dissimilar to the Sandia quartzites t o be correlative but that a reasonable correlation could be made with the Ab0 Formation, based on lithologies and sedimentary structures. Loughlin and Koschmann ( 1 9 4 2 ) , Kottlowski andothers (1956), andJaworski (1973) all noted limestone pebble conglomerates in the basal parts of the Ab0 Formation.…”
Section: Abo Formation'mentioning
confidence: 98%